Innover dans les forces spéciales - Jean Frances; Violette Larrieu (Socio, 2023)
How do military personnel succeed in designing or perfecting equipment useful to their mission? This paper will analyse the production of material innovations that are characterised by their ability to respond to an operational need, whose design is based on the skills, resources and abilities of soldiers in the field, and whose modelling and prototyping do not require the deployment of major research and development resources. We will show that these activities are based on an inverted form of “something on the side”. More generally, the question arises as to the capacity of an institution marked by the rigour of its hierarchy to make accessible to its personnel the margins of autonomy necessary for the engagement of frugal forms of technological research and development. Through an analysis centred on two case studies—a grenade-launching pole and an oxygen mask for dogs—of innovation by and for Special Forces operatives, we highlight the difficulty, for the military institution, of making an ‘innovation logic’ coexist with an ‘organisation logic’ and articulating them.